2019
DOI: 10.1007/s40544-018-0250-6
|View full text |Cite
|
Sign up to set email alerts
|

Response of grease film at low speeds under pure rolling reciprocating motion

Abstract: Using an optical interferometric technique, the grease film distribution under a pure rolling reciprocating motion is observed on a ball-disk test rig, to explore the transient response of grease, which is expected to fill the contact with thickener fiber and run for a long time under steady-state conditions. It is found that the reciprocating motion reduces the accumulation of the thickener fiber gradually with time. The maximum film thickness forms around the stroke ends. After 1,000 working cycles, very sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…This change exists as the surface speed varies within a range of 0.001-0.5 m/s in steady-state ZEV contact. That is to say, there is no critical entraining speed 9,10,12,13,31 under ZEV condition. Moreover, for experiments under transient condition, the disappearance of the thickener fiber is even faster, so it is not necessary to consider the influence of the thickener fiber on the film distribution.…”
Section: Resultsmentioning
confidence: 97%
“…This change exists as the surface speed varies within a range of 0.001-0.5 m/s in steady-state ZEV contact. That is to say, there is no critical entraining speed 9,10,12,13,31 under ZEV condition. Moreover, for experiments under transient condition, the disappearance of the thickener fiber is even faster, so it is not necessary to consider the influence of the thickener fiber on the film distribution.…”
Section: Resultsmentioning
confidence: 97%
“…As an important branch of transient EHL, reciprocation is a common form of motion. There have been a few experimental works for grease film distribution under transient conditions, such as the work by Li et al, 18,19 Wang et al, 20 and Han et al 21 Li et al 18,19 conducted an experimental investigation to explore crescent-shaped grease film in rolling and sliding micro-oscillation. They revealed the transient grease film variation in a reciprocating motion during one working cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the existence of the thickener, in the first several working periods, the variations of the film shape in the first and second stokes are different. Han et al 21 found that the reciprocating motion reduced the accumulation of the thickener gradually with time under the pure rolling condition. Another important point is that the thickener lumps affect the replenishment of grease.…”
Section: Introductionmentioning
confidence: 99%
“…8. The mechanisms of both shear degradation and starvation can induce film decay [52]. Shear degradation will cause both temporary and permanent apparent viscosity loss, hence reducing the film thickness, as shown for the initial film decay in Figs.…”
Section: Mechanisms Of Film Thickness Decaymentioning
confidence: 91%